Exploring potential roles of pharmacist in cancer palliative care unit of public tertiary care hospitals in Klang Valley, Malaysia / Ahlam Sundus - Sundus, Ahlam (2017)
Despite increased awareness measures taken, burden of cancer is increasing worldwide. In addition to conventional anti-cancer treatment, palliative care is indicated to improve the quality of life (Qol) of cancer patients and their families. With the evolution of pharmacy practice, the role of pharmacist was extended to introduce their services at clinical level. It was stipulated that in some parts of the world idea of integration of the pharmacist in this patient-care team was not fully embraced. This qualitative study aimed to explore potential roles of the clinical pharmacists in cancer palliative care settings in public tertiary care hospitals by highlighting potential areas suggesting integration of pharmacists in cancer palliative care team to improvise patient-oriented care. Face-to-face interviews were conducted from physicians, oncologists, nurses and pharmacists to explore their views regarding integration of pharmacists within cancer palliative care team. Cancer palliative care patients and their caregivers were also interviewed in order to bring forward their experiences during hospitalisation due to cancer. The interviews were conducted at Department of Oncology and Radiotherapy, Hospital Kuala Lumpur (HKL) and Palliative Care Unit (PCU), Hospital Selayang (HS). Interviews were audio-taped, transcribed verbatim which were then subjected to thematic analysis. Findings of the study suggested that doctors and nurses welcomed the idea of integration of the pharmacists within wards to constitute a triad for the improvement of patient care within cancer palliative care. Responding pharmacists mentioned about the scarcity of pharmacy staff at the respective study sites. On the other hand, it was found that majority of patients and caregivers were totally unaware of the existence of the pharmacist and their purpose in the oncology ward and PCU. However, policies are yet to be designed to give clinical pharmacy profession an adequate representation within hospitals.